Emerging patterns of Bangsa Malaysia in Anthony Burgess’ Time for a Tiger - Abd Razak, Farahanna; Bahar, Ida Baizura; Talif, Rosli (Australian International Academic Centre, 2016)
Time for a Tiger (1956), a novel by Anthony Burgess, is believed to have been overlooked in the Malaysian literary context. Existing scholarship has maintained that the central themes of Time for a Tiger are colliding cultures, clashes of religion and racial conflicts but, in spite of these themes, this paper attempts to argue that there are in fact emerging patterns of Bangsa Malaysia in Time for a Tiger, which in turn reflect the elements of unity among the rich mixture of multi-ethnic characters. Bangsa Malaysia is not only the first of the nine challenges listed in Vision 2020 as conceptualised by Dr. Mahathir Mohamad (1991), but also marks the first time the Malaysian government is officially putting forward a clear vision in building a nation, launched to create a oneness atmosphere among the ethnic groups, in hopes it will reduce, if not erase, the tension among them. This study reveals that there are indeed emerging patterns of Bangsa Malaysia depicted through a mixture of characters from various ethnicities, namely the Malays, the Chinese and the Indians, through the implementation of government policies, education, a change of mindset and personal judgement, patriotism and the unifying role of the monarchy. Additionally, the patterns do support the earlier stage of the formation of Bangsa Malaysia, namely tolerance.